CORRECTION OF COGNITIVE DISORDERS AMONG THE CHILDREN WITH ALLERGIC RHINITIS - A.Yu. Tomilova; L.S. Namazova-Baranova; L.M. Kuzenkova; O.I. Maslova ("Paediatrician" Publishers LLC, 2007)
To evaluate the status of the cognitive sphere among the children with the lengthy run of the perennial allergic rhinitis and elaborate the therapeutic tactics for the correction of the revealed disc orders, the researchers have examined 108 children aged between 14 and 15 years old. The research included patients with the exacerbation of the moderately severe or severe run of the perennial allergic rhinitis and length of the disease for no less than 3 years. As the basic therapy, the researchers prescribed mometasone nasal spray to all the children (Nasonex, Scheringcplough, USA). Before, in the course of and immediately right after the treatment, all the patients underwent the evaluation of the cognitive functions with the aid of the «binatest» and «mnemotest» test computer systems. The researchers determined the oxygen concentration in blood with handy pulse oximetry OXY 9. The research findings showed that 95,3% of the examined children suffered from the disorders of the cognitive functions. The application of the adequate anti-inflammatory therapy of the perennial allergic rhinitis effectively corrected the changes in the cognitive sphere of the children, suffering from the perennial allergic rhinitis. The oxygen concentration in blood of the children with the perennial allergic rhinitis remained normal at different stages of the disease. Thus, children, persistently suffering from the perennial allergic rhinitis, are recommended to undergo monitoring of the cognitive functions and prompt prescription of the adequate anti-inflammatory therapy of the disease.Key words: children, perennial allergic rhinitis, cognitive functions, treatment, mometasone.